Lost and found: the academic conference in pandemic and post-pandemic times. Issue 2 (3rd April 2021) - Donlon, Enda
Abstract : Conferences are widely recognised as a central component of academic life, providing important opportunities for dissemination of research, professional networking, and extending scholarship. Notwithstanding this, concerns are increasingly voiced around such factors as the environmental and sustainability aspects of conference travel and hosting, and issues of equity and access. The imposition of travel and congregation restrictions as a result of the Covid-19 pandemic has seen the suspension of in-person academic conferences throughout the world. This desk-based research study provides a timely opportunity to consider the challenges that this has precipitated, and the ensuing changes to the long-established and relatively consistent format that is employed for academic conferences. In doing so, it reflects upon what has been lost through the unavoidable abandonment of the traditional face-to-face conference during these unique times, but also what may have been found in terms of creative solutions, reimagined formats, and unexpected benefits that have arisen through the reconceptualisation of such events, and which may have wider implications for the academic conference in the post-pandemic world that awaits us.